IMPROVEMENT OF SERVICE IN HOSPITALITY INSTITUTIONS - Пушка, Ольга; Доценко, Виктор; Николенко, Надежда; Шаран, Лариса (SWorldJournal, 2020)
The paper considers the process of improving the level of service in hotels with the help of psychological training with elements of physiognomy and physiognomy for staff as one of the ways to increase the competitiveness of the enterprise. In an atmosphe